The case for mobile cancer care units: an NHS team's experience. Issue 5 (2nd May 2021) - Booth, Carl; Dyminski, Patricia; Rattray, Marcus; Quinn, Gemma; Nejadhamzeeigilani, Zaynab; Bickley, Leanda; Seymour, Tina
Abstract : A team of NHS clinicians explain how mobile cancer care units, provided by the charity Hope For Tomorrow, have helped them to deliver less disruptive cancer treatment and continue to care for patients during COVID-19.